2015
DOI: 10.1155/2015/803492
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Performance of Carbon Monolith/TiO2Composite

Abstract: The new and simple approach for deposition of catalytically active TiO 2 coating on carbon monolith (CM) carrier was presented. CM photocatalysts were impregnated with TiO 2 using titanium solution and thermal treatment, and their photocatalytic activity was investigated in the process of methylene blue (MB) photodegradation. For the purpose of comparison, CM composite photocatalysts were prepared by dip-coating method, which implies binder usage. The presence of TiO 2 on CM carrier was confirmed by Raman spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…To obtain highly reactive photocatalysts, in addition to TiO2 doping with nitrogen, photocatalysts can be combined with different carbon materials that play the role of catalysts. 1,[8][9][10] It was found that nitrogen doping combined with some carbon material as a carrier lead to an increase in the specific surface area of the material, as well as its photocatalytic activity under visible irradiation. 1 Previously, 8 we have used a simple method of hydrothermal synthesis to obtain highly reactive TiO2/carbon composites for photocatalytic degradation of selected organic pollutants, under UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain highly reactive photocatalysts, in addition to TiO2 doping with nitrogen, photocatalysts can be combined with different carbon materials that play the role of catalysts. 1,[8][9][10] It was found that nitrogen doping combined with some carbon material as a carrier lead to an increase in the specific surface area of the material, as well as its photocatalytic activity under visible irradiation. 1 Previously, 8 we have used a simple method of hydrothermal synthesis to obtain highly reactive TiO2/carbon composites for photocatalytic degradation of selected organic pollutants, under UV irradiation.…”
Section: Introductionmentioning
confidence: 99%